The impacts of landscape positions and land management practices on soil physicochemical properties in Mancha Galgo watershed, Rift Valley Basin of Ethiopia - Markos Mathewos; Biruk Hailu; Abiot Ketema (Geology, Ecology, and Landscapes)
The utmost pervasive and harmful procedure of land degradation is soil erosion by water. This study’s objective was to evaluate fanya juu affected particular soil characteristics and landscape positions in the Mancha Galgo watershed. Five-year-old fanya juu structure-treated fields were compared to un-conserved nearby land and assessed under slope gradients. The top 0–20 cm of the soil was sampled for a total of 18 composite soil samples, which were reproduced three times for each treatment in an “X” design square plot measuring 10 m × 10 m. Data were evaluated using the SPSS 20 version through one-way analysis of variance (ANOVA). Most of the examined soil characteristics, including clay, silt, sand, soil moisture content (SMC), soil organic matter (SOM), total nitrogen (TN), available phosphorus, exchangeable cations, and cation exchange capacity (CEC), showed significant (P≤0.05) changes between Fanya Juu-conserved land and the control plot. Regarding landscape positions, clay, silt, sand, BD, SOM, TN, available phosphorus, exchangeable basic cations, and CEC each demonstrated a significant variance (P≤0.05). For deeper knowledge of the impacts of ecological use of land, additional studies focused on the combined effects of both physical and biological SWC techniques through the inclusion of socio-economic factors are needed.